Premisses for a Public Policy to Foster the Creative Economy: the case of Ancine - Lima, Roberto Gonçalves (Brazilian Journal of Operations & Production Management, 2018)
The purpose of this paper is to identify the premisses that have oriented the construction process of structuring public policies to the audiovisual domain draw on the ten years managerial experience of Brazil’s National Cinema Agency (Ancine), also seeking to take a look at how such experience can bring perspectives to the formulation and management of policies directed towards the Creative Economy.